2020
DOI: 10.1210/clinem/dgaa347
|View full text |Cite
|
Sign up to set email alerts
|

An Intronic HCP5 Variant Is Associated With Age of Onset and Susceptibility to Graves Disease in UK and Polish Cohorts

Abstract: Context The genetic background of young-onset Graves disease (GD) remains largely unknown. An intronic variant in human leukocyte antigen (HLA) complex P5 (HCP5) has previously been associated with GD susceptibility and age of onset in a cohort of Polish patients. Objective We aimed to investigate the association of the HCP5 variant rs3094228 with GD susceptibility and age of onset in a UK cohort and conduct a meta-analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…TG and TSHR) (13,14,15). HCP5 polymorphisms have been associated with a younger age at GD onset (16,17). GD is associated with the occurrence of other autoimmune disorders such as type I diabetes mellitus, celiac disease and vitiligo and is more common in Down syndrome (4,18).…”
Section: Definitive Treatment In Pediatric Gd -Radioiodine (Rai)mentioning
confidence: 99%
“…TG and TSHR) (13,14,15). HCP5 polymorphisms have been associated with a younger age at GD onset (16,17). GD is associated with the occurrence of other autoimmune disorders such as type I diabetes mellitus, celiac disease and vitiligo and is more common in Down syndrome (4,18).…”
Section: Definitive Treatment In Pediatric Gd -Radioiodine (Rai)mentioning
confidence: 99%
“…Younger GD patients tend to have more severe hyperthyroidism at presentation when compared to adults [ 9 ] and this may be partly related to the nature of the underlying immune dysfunction. Recent data have shown that the human leukocyte antigen (HLA) complex P5 (HCP5) polymorphism is independently associated with GD susceptibility and age of onset [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The locus with the strongest evidence for a role in gout was CNVR1, which is dominated by deletion. Genetic (SNV) associations identified by GWAS for immune-mediated disease have been reported at this locus, including HIV infection ( 32 ) and autoimmune diseases such as Grave’s disease ( 33 ) and systemic lupus erythematosus ( 34 ). CNVs that overlap CNVR1 have been reported to be associated with nasopharyngeal carcinoma predisposition ( 35 , 36 ), type 1 diabetes ( 37 ) and schizophrenia or bipolar disorder ( 38 ) and, now, gout.…”
Section: Discussionmentioning
confidence: 99%